Honduras Maize Wholesaler Survey - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
Honduras maize wholesaler survey is the study of the wholesalers in the maize value chain in Honduras. These data allow quantifying the extent of food loss in the wholesaler level using consistent approaches that are comparable across commodities and regions. They also enable characterizing the nature of food loss, specifically the production stages and the particular processes at which loss is incurred.